2012
DOI: 10.1016/s1413-8670(12)70284-2
|View full text |Cite
|
Sign up to set email alerts
|

Seronegative cat-scratch disease diagnosed by PCR detection of Bartonella henselae DNA in lymph node samples

Abstract: Cat scratch disease (CSD), the typical clinical manifestation of Bartonella infections usually follows a typical benign self-limited course. Nevertheless, a variety of unusual clinical manifestations and confusing imaging features can lead to misinterpretations and render the disease a diagnostic dispute. Routine laboratory tests exhibit varying reported sensitivity and are usually unhelpful in diagnosis, as serology fails in terms of specificity and/or sensitivity. Herein we report a case of seronegative Bart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
0
15
1
Order By: Relevance
“…Bartonella serology was supportive of B. henselae infection in the mother, but not in the son, further supporting reports of seronegative Bartonella sp. bacteremia in human patients [10,11,78,79]. Also, despite improvements in PCR sensitivity, immunohistochemical methods are useful to facilitate the visualization of Bartonella species in patient tissue specimens.…”
Section: Resultsmentioning
confidence: 99%
“…Bartonella serology was supportive of B. henselae infection in the mother, but not in the son, further supporting reports of seronegative Bartonella sp. bacteremia in human patients [10,11,78,79]. Also, despite improvements in PCR sensitivity, immunohistochemical methods are useful to facilitate the visualization of Bartonella species in patient tissue specimens.…”
Section: Resultsmentioning
confidence: 99%
“…In our case, histopathologically, the lesion showed suppurative granulomatous inflammation, and the WS stain detected clumps of bacilli, highly suggestive of CSD but not definitive [21,22]. Chondrogiannis et al described a sero-negative CSD case confirmed by PCR and mentioned limitations of histopathology [21].…”
Section: Letter To the Editormentioning
confidence: 73%
“…Chondrogiannis et al described a sero-negative CSD case confirmed by PCR and mentioned limitations of histopathology [21]. However, they also mentioned histopathologic examination of lymph nodes is crucial for exclusion [21,23]. …”
Section: Letter To the Editormentioning
confidence: 99%
“…The diagnosis of CLD is even more complex when tick-borne coinfections occur in association with Lyme disease [ 105 ], which is the rule rather than the exception [ 106 ]. Routine laboratory tests exhibit varying reported sensitivity and are usually unhelpful in diagnosis, as serology fails in terms of specificity and/or sensitivity [ 107 ]. Clinically relevant coinfections include Bartonella species [ 105 ], Babesia [ 108 ], Anaplasma [ 109 ], Rickettsia [ 110 ], Yersinia enterocolitica , Chlamydophila pneumoniae , Chlamydia trachomatis , Mycoplasma pneumoniae [ 105 ], and tick-borne encephalitis virus, amongst others [ 108 , 111 ].…”
Section: Resultsmentioning
confidence: 99%